Small business revolution how owners and entrepreneurs can succeed - McCarthy, Barry C. (Ascent Audio, 2022)
In Small Business Revolution president and CEO of Deluxe Corp. Barry C. McCarthy delivers a stirring combination of uplifting narrative and small business instruction manual. Featuring inspiring stories from the company's 106-year history and anecdotes from its Emmy-nominated TV show Small Business Revolution, this book offers listeners the opportunity to learn how to grow and thrive in their business in any environment, from a booming economy to a post-pandemic marketplace. Whether you're just starting to plan your new business or you are a seasoned veteran in the small business trenches, you'll discover a wealth of information to help you structure your business to reach customers, find talent, understand finances, and so much more. You'll find guidance on: how to get your costs in line when your expenses have changed; mastering new tools to manage payments and payroll, including contactless and remote payments; maintaining relationships with your existing customers while reaching out to new ones; how to manage cash; how to retain employees through lean times; and more. Perfect for the millions of individuals who plan to start or run a small business during one of the most challenging times in recent memory, Small Business Revolution is an indispensable guide to helping your enterprise survive and succeed during unprecedented challenges.
Online resource; title from title details screen (O'Reilly, viewed May 3, 2022)
Keywords: Small business -- Management; Small business -- Finance; Small business -- Growth; Petites et moyennes entreprises; Gestion; Petites et moyennes entreprises; Finances; Petites et moyennes entreprises; Croissance; Small business; Finance; Small business; Growth; Small business; Management; Downloadable audio books; Audiobooks; Livres audio